2023
DOI: 10.1186/s12902-023-01351-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and contributing risk factors of coronavirus disease 2019 infection in patients with metabolic syndrome

Abstract: Background Components of metabolic syndrome (MetS) was reported to contribute to severe and worse outcomes of coronavirus disease 2019 (COVID-19). Hereby, we evaluated the association of MetS and its components with susceptibility to COVID-19. Methods Here, 1000 subjects with MetS were recruited that were diagnosed via the International Diabetes Federation (IDF) criterion. Real-time PCR was exerted to detect SARS-CoV-2 in the nasopharyngeal swabs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…The latest evidence suggested that increased and uncontrolled inflammation plays a pivotal role in the pathogenesis of COVID-19 [ 12 , 13 ]. Numerous molecules in the immune system lead to inflammation, and the formation of inflammasomes and inflammatory cytokines are essential in these processes [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest evidence suggested that increased and uncontrolled inflammation plays a pivotal role in the pathogenesis of COVID-19 [ 12 , 13 ]. Numerous molecules in the immune system lead to inflammation, and the formation of inflammasomes and inflammatory cytokines are essential in these processes [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to highlight that lifestyle habits directly affect the quality of life and glycemic control or lack thereof, as although most interventions to control DM involve the use of hypoglycemic drugs, dietary changes and physical activity are the main measures to combat insulin resistance 15,16 . The antecedents to the appearance of metabolic syndrome, such as inadequate diet and sedentary lifestyle, influence the clinical condition and consequently the appearance of cardiovascular diseases and type 2 DM 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…É importante ressaltar que os hábitos de vida implicam diretamente na qualidade de vida e no controle glicêmico ou falta dele, pois apesar da maior parte das intervenções para controle do DM envolver o uso de hipoglicemiantes, a mudança alimentar e prática de atividade física são as principais medidas no combate à resistência insulínica 15,16 . Os antecedentes ao aparecimento da síndrome metabólica, como a alimentação inadequada e sedentarismo influenciam na condição clínica e em consequência ao aparecimento de doenças cardiovasculares e DM tipo 2 15,16 .…”
Section: Discussionunclassified